Identification and characterization of micrornas involved in the invasion and migration properties of lung, prostate and breast cancer cells / Yap Seow Hui - Yap, Seow Hui (2012)

(untitled)
Primary cancer is often treatable by radiation therapy, chemotherapy or surgery, but tumour invasion and metastasis still remains the most challenging problem to cancer patients, causing death through organ damage or treatment complications. Past researches have focused on these issues, but no major breakthroughs have been achieved to prevent tumour metastasis. Dysregulation in the expression of short non-protein coding microRNAs (miRNAs) found contributes toward the initiation and progression of cancer through their capability to regulate multiple target genes. In this study, four pairs of high and low invasiveness sub-cell lines distinct in invasion and migration properties were established from their heterogeneous parental lung cancer cell line of A549, prostate cancer cell line of PC-3, breast cancer cell lines of MDA-MB-231 and MCF7 using serial transwell invasion approach. To gain insight into the molecular mechanisms that contribute to cancer migration and invasion, miRNA microarray was conducted on the three paired-sub cell lines of A549, PC-3 and MCF7. Lists of significant differentially expressed miRNAs between the three paired cell lines were identified and a subset of miRNAs from A549 was validated by Real-Time PCR. Through pathway enrichment analysis, a hypothetical pathway model describing A549 lung cancer metastasis was generated highlighting the network interaction of miRNAs and their gene targets. All these miRNAs act in concert in modulating three main pathways which were the non-canonical Wnt/planar cell polarity (PCP), transforming growth factor-β (TGF-β) and integrin signalling cascade to promote lung cancer migration and invasion. These results provide potential candidate metastatic markers for non-small cell lung cancer classification, prognosis and a possible therapeutic effect through targeting these miRNAs to control lung tumour invasion and metastasis.